Advanced Monitoring of H 2 S Injection through the Coupling of Reactive Transport Models and Geophysical Responses - Ciraula, Daniel A; Kleine-Marshall, Barbara I; Galeczka, Iwona M; Lévy, Léa (Environmental science & technology, 2024)
Hydrogen sulfide (H S), an environmentally harmful pollutant, is a byproduct of geothermal energy production. To reduce the H S emissions, H S-charged water is injected into the basaltic subsurface, where it mineralizes to iron sulfides. Here, we couple geophysical induced polarization (IP) measurements in H S injection wells and geochemical reactive transport models (RTM) to monitor the H S storage efforts in the subsurface of Nesjavellir, one of Iceland's most productive geothermal fields. An increase in the IP response after 40 days of injection indicates iron-sulfide formation near the injection well. Likewise, the RTM shows that iron sulfides readily form at circumneutral to alkaline pH conditions, and the iron supply from basalt dissolution limits its formation. Agreement in the trends of the magnitude and distribution of iron-sulfide formation between IP and RTM suggests that coupling the methods can improve the monitoring of H S mineralization by providing insight into the parameters influencing iron-sulfide formation. In particular, accurate fluid flow parameters in RTMs are critical to validate the predictions of the spatial distribution of subsurface iron-sulfide formation over time obtained through IP observations. This work establishes a foundation for expanding H S sequestration monitoring efforts and a framework for coupling geophysical and geochemical site evaluations in environmental studies.